Answer:
2
Explanation:
If y = 1
2x - 3 = 1
Which means 2x must be 4, because we know 4 - 3 = 1
so x must be 2, because the answer has to be something that makes 4 when we times it by 2.
first thing you gotta do is substitute x with -1 then you do the work first you gotta know your order of operation which is PEMDAS what that stands for is perentice exponent multiplication division addition and subtraction so then what you do first is 2*-1+3 2*-1=-2+3=1 and that is the answer you are WELCOME.
5.1m questions
6.7m answers